2012
DOI: 10.1208/s12249-012-9760-0
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Investigations and Stability Studies of Amorphous Gliclazide

Abstract: Abstract. Gliclazide (GLI), a poorly water-soluble antidiabetic, was transformed into a glassy state by melt quench technique in order to improve its physicochemical properties. Chemical stability of GLI during formation of glass was assessed by monitoring thin-layer chromatography, and an existence of amorphous form was confirmed by differential scanning calorimetry and X-ray powder diffractometry. The glass transition occurred at 67.5°C. The amorphous material thus generated was examined for its in vitro dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 41 publications
(57 reference statements)
1
27
0
1
Order By: Relevance
“…The improved stability of amorphous ITR in presence of sacrificial excipient could be explained on the basis of combination of several effects: (a) elevation of T g ; (b) hydrogen bonding between the drug and the polymer; (c) antiplasticizing effect of the polymers. 15 Therefore, it can be concluded that the sacrificial excipients could be useful to prevent devitrification process of an amorphous drug by decreasing the plasticizing effect of adsorbed water.…”
Section: Moisture Uptake Studymentioning
confidence: 99%
“…The improved stability of amorphous ITR in presence of sacrificial excipient could be explained on the basis of combination of several effects: (a) elevation of T g ; (b) hydrogen bonding between the drug and the polymer; (c) antiplasticizing effect of the polymers. 15 Therefore, it can be concluded that the sacrificial excipients could be useful to prevent devitrification process of an amorphous drug by decreasing the plasticizing effect of adsorbed water.…”
Section: Moisture Uptake Studymentioning
confidence: 99%
“…It also shows slow dissolution rate due to its hydrophobicity and poor wettability (Jondhale et al, 2012;Grbic et al, 2011;Biswal et al, 2008). Therefore, GLZ exhibits slow gastrointestinal absorption rate and high inter-subject variation for its bioavailability (Biswal et al, 2008;Jondhale et al, 2012;Biswal et al, 2009a;Palmerand Brogden, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, key limitations associated with the amorphous phase need to be addressed are poor thermodynamic stability and higher chemical reactivity which may be attributed to stress favored devitrification during manufacturing operations and/or storage (Pokharkar et al, 2006). Further, water vapor, a plasticizer, plays an important role in adversely affecting physico-chemical properties of amorphous solids (Jondhale et al, 2012). Thus, to fully exploit solubility advantages of amorphous drugs, there is a definite need to stabilize them in solid state.…”
Section: Introductionmentioning
confidence: 99%